2022
DOI: 10.1186/s12872-022-02673-y
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride glucose index exacerbates the risk of future cardiovascular disease due to diabetes: evidence from the China Health and Retirement Longitudinal Survey (CHARLS)

Abstract: Objective We aimed to investigate the effect of the triglyceride glucose (TyG) index on the association between diabetes and cardiovascular disease (CVD). Methods Data from 6,114 individuals were extracted and analyzed from the China Health and Retirement Longitudinal Survey (CHARLS) from 2011 to 2018. Logistic regression analyses were conducted to assess the relationship between diabetes and CVD across the various TyG index groups. The statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…The current study explores the relationship between the TyG index and the risk of developing cardiovascular disease in the Chinese middle-aged and elderly population in a large-scale prospective cohort study from the China health and retirement longitudinal study (CHARLS). This study is a follow-up of our previous study from the same cohort, which demonstrated that the elevated TyG index strengthens the association between diabetes and cardiovascular disease [11].…”
Section: Introductionsupporting
confidence: 64%
“…The current study explores the relationship between the TyG index and the risk of developing cardiovascular disease in the Chinese middle-aged and elderly population in a large-scale prospective cohort study from the China health and retirement longitudinal study (CHARLS). This study is a follow-up of our previous study from the same cohort, which demonstrated that the elevated TyG index strengthens the association between diabetes and cardiovascular disease [11].…”
Section: Introductionsupporting
confidence: 64%
“… 12 In addition, the study discovered that high TyG index level could increase the risk of CVD in DM patients. 9 The report indicated that the prevalence of CVD caused by the high level of the TyG index was 1.25-fold that of the low TyG index level. 27 Similarly, our study discovered that the TyG index was an independent hazard factor for new-onset hypertension.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Furthermore, the TyG index has been confirmed to be a marker of insulin resistance (IR). 8 However, recent studies confirmed that the TyG index could increase cardiovascular disease hazard and result in atherosclerosis and arterial stiffness, 9–12 which might be linked to IR. 13–15 Moreover, among the many risk factors of hypertension, atherosclerosis and arterial stiffness play a significant role in hypertension development, 16–18 and their ability to contribute to development of hypertension may increase with age-related physiological alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hong et al suggested its potential in early cardiovascular event detection for those aged 40 and older [ 34 ]. Research on Chinese middle-aged and elderly diabetic patients revealed an elevated TyG index associated with an increased CVD risk [ 35 ]. Moreover, a study of individuals over 65 exhibited a robust correlation between the TyG index and all-cause/CVD mortality [ 36 ].…”
Section: Discussionmentioning
confidence: 99%